Company's Strategy To Maintain The Quality Of Human Resources In New Normal In Retail And Multinational Companies - Anik Ida Iryani; Rizka Taurina Rachmawati; Vika Lusi Apriani; Sapto Supriyanto (Institute of Computer Science (IOCS), 2021)
Covid-19, which is still a pandemic today, brings a change in lifestyle to the social order. People are required to adopt new habits (new normal) to be able to live productively. The new normal era began to be enforced by the government with the issuance of the Decree of the Minister of Health. Ensure a quality work process for each company by utilizing human resources as best as possible with some considerations. The study of retail companies and national DNA, to know and understand the strategy of national private companies to improve the performance of its employees in the face of the new era of normal As well as the process of multinational private companies to improve the performance of its employees at the beginning of the new normal era. The research will impact the development efforts of a healthy working environment by creating an office with the concept of open space, modern, ecofriendly and high-technology. In addition, the idea of 3T (Right Quality, On Time, On Target) and 3K (Communication, Coordination, Collaboration) must also be applied so that the talents can make a positive contribution to the company both in the era of covid 19 and in the new normal period.